2006
DOI: 10.1021/ja061460g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amphiphilic Superparamagnetic Ferrite/Block Copolymer Hollow Submicrospheres

Abstract: Self-assembly can be a powerful, but simple, synthetic method for the fabrication and surface modification of nanometer- to micrometer-sized hollow spheres. Here we report a facile route for preparation of submicrometer ferrite hollow spheres which are amphiphilic and superparamagnetic. This unique approach involves the formation of ferrite nanocrystals and the simultaneous self-assembly of nanocrystals and block copolymer PEO-PPO-PEO into hollow spheres. Furthermore, this approach is general for the preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(83 citation statements)
references
References 22 publications
2
78
0
Order By: Relevance
“…The PVP molecules play an important role in preventing the spheres from agglomerating as many polymer molecules do in the formation of other spherical species. [12,33] However, when we used non-PVP surfactants, such as poly(ethylene glycol), poly(vinyl alcohol), poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) for the preparation of CSCS, no spherical structures were obtained under the same reaction conditions. This observation suggests that the PVP molecules may be unique for the formation of the CSCS in the current reaction system.…”
Section: Resultsmentioning
confidence: 99%
“…The PVP molecules play an important role in preventing the spheres from agglomerating as many polymer molecules do in the formation of other spherical species. [12,33] However, when we used non-PVP surfactants, such as poly(ethylene glycol), poly(vinyl alcohol), poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) for the preparation of CSCS, no spherical structures were obtained under the same reaction conditions. This observation suggests that the PVP molecules may be unique for the formation of the CSCS in the current reaction system.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al reported a one-step solvothermal route to prepare superparamagnetic firrite/polymer hybrid hollow spheres. [244] This synthesis involves formation of ferrite nanoparticles and simultaneous self-assembly of nanoparticles and PEO-PPO-PEO into hollow spheres. Polymer hollow nanospheres can also be derived from the self-assembled core/shell polymer micelles.…”
Section: Reviewmentioning
confidence: 99%
“…Although great efforts have been made towards the development of template-free routes for the preparation of hollow structures [13][14][15], template-directed synthetSchool of Chemistry and Chemical Engineering, Shanghai Jiao Tong University, Shanghai 200240, China * Corresponding authors (email: xinhaoli@sjtu.edu.cn (Li XH); chemcj@sjtu.edu.cn (Chen JS)) ic methods have been established as one of the most effective and controllable methods for synthesizing hollow structures [16]. The most commonly used templates can broadly be divided into two categories: hard templates and soft templates.…”
Section: +mentioning
confidence: 99%
“…The void space can also act as a catalyst container for embedded fine metal nanoparticles to extend their life-time [9,10]. Moreover, the thin shell of hollow micro-and nanoscale structures can facilitate charge transfer to surface active sites [11], which implies that they have great potential as highly efficient photocatalysts for water splitting and artificial photosynthesis [12].Although great efforts have been made towards the development of template-free routes for the preparation of hollow structures [13][14][15], template-directed synthetSchool of Chemistry and Chemical Engineering, Shanghai Jiao Tong University, Shanghai 200240, China * Corresponding authors (email: xinhaoli@sjtu.edu.cn (Li XH); chemcj@sjtu.edu.cn (Chen JS)) ic methods have been established as one of the most effective and controllable methods for synthesizing hollow structures [16]. The most commonly used templates can broadly be divided into two categories: hard templates and soft templates.…”
mentioning
confidence: 99%